Analisis Penerapan Model Pembelajaran Project Based Learning Pada Materi Pendidikan Pancasila dan Kewarganegaraan di Sekolah Dasar - Mu'afida, Mutiara Natasya; Rondli, Wawan Shokib (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
In elementary school learning, PPKn material has a very important position in improving and preparing students to become reliable human beings and also as a learning that directs students to become good, skilled, intelligent students and also with character based on values. in Pancasila and the 1945 Constitution. Project Based Learning or commonly called PJBL is a learning model that emphasizes student activity in solving open-ended problems, the application of this PJBL learning model is that students are involved in a project that will be carried out Then students produce a certain authentic product. This research aims to analyze the application of the Project Based Learning (PJBL) learning model. This research uses a qualitative descriptive research method. Data collection techniques were carried out using interview and observation techniques. The subjects of this research were class IV students at SD Negeri 3 Kesambi and class IV teachers at SD Negeri 3 Kesambi. Based on research conducted, the use of the Project Based Learning (PJBL) learning model at SD Negeri 3 Temulus, especially in class IV, can foster student interest and interest in Civics subjects so that learning outcomes are high, even though there are several obstacles experienced by teachers.